PENGARUH MEDIA PEMBELAJARAN AUDIO VISUAL BERBASIS WINDOWS MOVIE MAKER TERHADAP KEMAMPUAN MENGANALISIS SEJARAH SISWA KELAS X IPA SEMESTER GENAP DI SMA MUHAMMADIYAH 1 METRO TAHUN PELAJARAN 2016/2017 - Evi Ernasari; Kian Amboro (UNIVERSITAS MUHAMMADIYAH METRO, 2017)
The purpose of this study to determine the effect of the use of audio-visual learning media windows movie maker based on the ability to analyze the history of science students in class X SMA Muhammadiyah 1 Metro second semester of the school year 2016/2017. This research uses quasi-experimental research (quasi exsperiment) with type Nonequivalent control group design. the sample was selected using random cluster sampling (taking classes at random). This research activity using audiovisual media based on windows movie maker where the ability to analyze historical results of students using audio-visual media-based learning windows movie maker is higher than the use of media power point. This can be evidenced mealui the acquisition value of the average post-test between the experimental class students and students of the control class. That the average yield of the ability to analyze the history of the experimental class and the control class earn 78.47 72.55 based on the average value obtained that the average value of 5.92 experimental class larger than the control class. Based on these calculations it can be concluded that the experimental class learning higher than the control class. The conclusion of this study is no influence of the use of audio-visual learning media windows movie maker based on the ability to analyze History Class X Science Semester at SMA Muhammadiyah 1 Metro in the academic year 2016/2017.